ANALISIS AMANAT DALAM PUISI “PANGGUNG SANDIWARA” KARYA IKA MUSTIKA - Vivin Kusmiati; Nursiti Fatimah; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This research aims to find out the message contained in the poem "PANGGUNG SANDIWARA" By Ika Mustika. This research can be useful for the readers and the writers in building a literary work. To improve the reader's ability in analyzing a poem. The method used in this research is a descriptive qualitative method that is by presenting the results of research with the form of words. The source obtained from the book Mustika 40 Puisi. The analysis results found the element of poetry builder one of which is the message. The message is the kindness message that the author conveys through the story. This message itself is closely related to the cause and effect. The message we can take from poetry can be applied in daily life. Therefore, in making poetry a complete work, the message is very important.